Diskursus Minoritas Melalui Kurikulum, Buku dan Kultur di Sekolah - Muaddab, Hafis (Progresiva : Jurnal Pemikiran dan Pendidikan Islam, 2020)
This paper is concerned to explain minority discourse through the curriculum, books, and culture in schools. Conflicts between minorities and majorities can occur in Indonesia, whenever and wherever, whether motivated by differences in ethnicity, ethnicity, religion, or groups. The problem is whether the education sector has contributed to its prevention aspects. Moreover, the national education curriculum is still oriented on cognitive abilities, while aspects of social intelligence have not been touched. The various references available have also not opened students' awareness in accepting the existence of minority groups. School education still merely raises passive tolerance, has not yet fostered active tolerance. Educational orientation must be stressed on the importance of a transformative, dialogic approach and inclusive to diversity. Then, it also refers back to the achievement of Ki Hajar Dewantara's ideals of liberation and humanizing education.Â